Silencing of Long Noncoding RNA AK139328 Attenuates Ischemia/Reperfusion Injury in Mouse Livers - Chen, Zhenzhen (Public Library of Science, 2013)
Recently, increasing evidences had suggested that long noncoding RNAs (LncRNAs) are involved in a wide range of physiological and pathophysiological processes. Here we determined the LncRNA expression profile using microarray technology in mouse livers after ischemia/reperfusion treatment. Seventy one LncRNAs were upregulated, and 27 LncRNAs were downregulated in ischemia/reperfusion-treated mouse livers. Eleven of the most significantly deregulated LncRNAs were further validated by quantitative PCR assays. Among the upregulated LncRNAs confirmed by quantitative PCR assays, AK139328 exhibited the highest expression level in normal mouse livers. siRNA-mediated knockdown of hepatic AK139328 decreased plasma aminotransferase activities, and reduced necrosis area in the livers with a decrease in caspase-3 activation after ischemia/reperfusion treatment. In ischemia/reperfusion liver, knockdown of AK139328 increased survival signaling proteins including phosphorylated Akt (pAkt), glycogen synthase kinase 3 (pGSK3) and endothelial nitric oxide synthase (peNOS). Furthermore, knockdown of AK139328 also reduced macrophage infitration and inhibited NF-κB activity and inflammatory cytokines expression. In conclusion, these findings revealed that deregulated LncRNAs are involved in liver ischemia/reperfusion injury. Silencing of AK139328 ameliorated ischemia/reperfusion injury in the liver with the activation of Akt signaling pathway and inhibition of NF-κB activity. LncRNA AK139328 might be a novel target for diagnosis and treatment of liver surgery or transplantation.